Synthesis, Spectral, Antimicrobial and Thermogravimetric Studies of Th(IV) and UO2(VI) Metal Complexes with Schiff Base - Agnihotri, Sonal; Arora, Kishor (Asian Journal of Chemistry, 2010)
Schiff base was obtained using 2-nitro benzaldehyde and 2-amino pyridine to prepare new complexes of thorium(IV) and dioxouranium(VI) metals by various anions. The synthesized ligands and complexes were analytically studied through spectral studies, elemental analysis and conductance measurements. The complexes showed various co-ordination number and their toxic effects to bacterial and fungal genus was studied by two different methods of measurement.